2021
DOI: 10.1245/s10434-021-09739-9
|View full text |Cite|
|
Sign up to set email alerts
|

Morbidity and Outcomes After Distal Pancreatectomy for Primary Retroperitoneal Sarcoma: An Analysis by the Trans-Atlantic Australasian Retroperitoneal Sarcoma Working Group

Abstract: University Hospital Birmingham 9 (3.2) 67 (5.8) University Hospitals Gasthuisberg Leuven 11 (3.9) 53 (4.6) University of Ottawa 9 (3.2) 33 (2.9) Veneto Institute of Oncology 2 (0.7) 13 (1.1) Yale University 3 (1.1) 8 (0.7) Total 280 1114 RPS, retroperitoneal sarcoma Distal Pancreatectomy for Retroperitoneal Sarcoma

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 18 publications
4
17
0
Order By: Relevance
“…In their study, 86% (43/50) of patients underwent DP, and rates of complications and severe complications were 64% (32/50) and 28% (14/50), respectively. Also, POPF occurred in 14% (7/50) of cases, with 12% (6/50) of cases being grade B and 2% (1/50) of cases being grade C. The Trans-Atlantic Australasian Retroperitoneal Sarcoma Working Group (TARPSWG) retrospectively reviewed 280 cases in a multicenter study and reported outcomes after DP for RPS ( 7 ). In their study, rates of complications and severe complications were 62.5% (175/280) and 39.6% (111/280), respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In their study, 86% (43/50) of patients underwent DP, and rates of complications and severe complications were 64% (32/50) and 28% (14/50), respectively. Also, POPF occurred in 14% (7/50) of cases, with 12% (6/50) of cases being grade B and 2% (1/50) of cases being grade C. The Trans-Atlantic Australasian Retroperitoneal Sarcoma Working Group (TARPSWG) retrospectively reviewed 280 cases in a multicenter study and reported outcomes after DP for RPS ( 7 ). In their study, rates of complications and severe complications were 62.5% (175/280) and 39.6% (111/280), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…( 8 ) in 34% (17/50), and the French Sarcoma Group ( 24 ) in 15.2% (5/33), respectively. In addition, the TARPSWG analyzed only patients who underwent DP and confirmed microscopic pancreatic invasion in 38.2% (107/280) ( 7 ). Similarly, in our study, microscopic pancreatic invasion was confirmed in 42.4% (14/33) of patients who underwent DP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Major vascular resection of the inferior vena cava, aorta and its major branches are intermittently required and indicated if reconstruction is possible [ 78 ]. Naturally, such benefit must be weighed against the risks of morbidity of resecting additional structures, such as the duodenum or pancreas necessitating pancreaticoduodenectomy, diaphragm or motor nerves, and kidney, all associated with possible significant morbidity [ 79 , 80 , 81 , 82 ]. Additional areas of concern preclude surgical resection include the superior mesenteric vessels, portal and hepatic vessels, pericardium and mediastinal structures, spinal cord and nephrectomy particularly if the contralateral kidney is non-functional [ 79 , 80 , 81 , 83 , 84 ].…”
Section: Management Of Primary Retroperitoneal Sarcomamentioning
confidence: 99%